2022
DOI: 10.3389/fnbot.2022.1072365
|View full text |Cite
|
Sign up to set email alerts
|

A CW-CNN regression model-based real-time system for virtual hand control

Abstract: For upper limb amputees, wearing a myoelectric prosthetic hand is the only way for them to continue normal life. Even until now, the proposal of a high-precision and natural performance real-time control system based on surface electromyography (sEMG) signals is still challenging. Researchers have proposed many strategies for motion classification or regression prediction tasks based on sEMG signals. However, most of them have been limited to offline analysis only. There are even few papers on real-time contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…d) Deep Learning: Study [163] achieved low-latency real-time prediction with the Channel-wise-CNN model, where each kernel corresponded to an sEMG channel, and enabled transfer learning by updating only the fully connected layers. LSTMbased [164] found that using all sEMG channels outperformed one-to-one mapping.…”
Section: ) Hand-wrist Jointsmentioning
confidence: 99%
“…d) Deep Learning: Study [163] achieved low-latency real-time prediction with the Channel-wise-CNN model, where each kernel corresponded to an sEMG channel, and enabled transfer learning by updating only the fully connected layers. LSTMbased [164] found that using all sEMG channels outperformed one-to-one mapping.…”
Section: ) Hand-wrist Jointsmentioning
confidence: 99%